A novel risk score to predict cardiovascular complications in patients with coronavirus disease 2019 (COVID‐19): A retrospective, multicenter, observational study. Issue 4 (24th September 2020) - Huang, Dong; Yang, Huan; Yu, He; Wang, Ting; Yao, Rong; Liang, Zongan
Abstract: Background: We conducted this study to explore a novel risk score to predict cardiovascular complications in patients with coronavirus disease 2019 (COVID‐19). Methods: The current study was a retrospective, multicenter, observational study. The clinical data of COVID‐19 patients at admission were collected. Patients were randomly divided into training set and testing set (70% vs. 30% of patients). Independent risk factors were identified via logistic regression analysis. Results: Finally, 1207 patients were included. Ten independent risk factors associated with cardiovascular complications were identified in training set: male (odds ratio [OR]: 1.84; 95% confidence interval [CI]: 1.18, 2.85), age ≥ 60 years old (OR: 2.01; 95% CI: 1.3, 3.2), cough (OR: 1.86; 95% CI: 1.16, 3), chronic heart disease (OR: 2.3; 95% CI: 1.19, 4.46), lymphocyte count ≤1.1 × 10 9 /L at admission (OR: 1.60; 95% CI: 1.03, 2.47), blood urea nitrogen ≥7 mmol/L at admission (OR: 2.14; 95% CI: 1.27, 3.62), estimated glomerular filtration rate ≤90 ml/min/1.73 m 2 at admission (OR: 2.08; 95% CI: 1.13, 3.83), activated partial thromboplastin time ≥37 s (OR: 3.07; 95% CI: 1.37, 6.86), D‐dimer ≥ 0.5 mg/L (OR: 2.12; 95% CI: 1.33, 3.36) and procalcitonin ≥0.5 μg/L (OR: 3.58; 95% CI: 1.40, 9.14). The area under curve of ROC curve was 0.773 (95% CI: 0.723, 0.822; p < .01). The risk score had robustness and generalizability after validation. Cardiovascular complications were significantly associated with poorer survivals (log‐rank test: p < .001). Conclusions: We developed and validated a novel risk score, which has a promising predictive capacity for cardiovascular complications in COVID‐19 patients. Abstract : We developed and validated a novel risk score, which has a promising predictive capacity for cardiovascular complications in coronavirus disease 2019 (COVID‐19) patients. Cardiovascular complications were significantly associated with poorer survival (log‐rank test: p < .001).